2018
DOI: 10.1016/j.exphem.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Inverse and correlative relationships between TRIBBLES genes indicate non-redundant functions during normal and malignant hemopoiesis

Abstract: TRIBBLES pseudokinases (TRIB1, TRIB2, and TRIB3) are important regulators of normal and malignant hemopoiesis. The relative abundance of each TRIBBLES family member may be important for distinct oncogenic or tumor suppressor functions. We map the expression profiles of TRIB1, TRIB2, and TRIB3 in human and murine hemopoietic stem, progenitor and mature cells, and in human leukemia datasets. Our data show that TRIB1-TRIB2 have an inverse expression relationship in normal hemopoiesis, whereas TRIB1-TRIB3 have a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…At the level of hematopoiesis TRIB2 plays an important role mainly through the degradation of C/EBP-α. It has been observed that TRIB2 is overexpressed during thymus development, and in B cells, natural killers, and CD4+ T cells and to a lesser degree in CD8+ T cells [ 19 ]. Additionally, TRIB2 is expressed in early hematopoietic progenitors and erythroid precursors, and the deletion of TRIB2 mainly affected erythroid lineage development.…”
Section: Trib2 In Health and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…At the level of hematopoiesis TRIB2 plays an important role mainly through the degradation of C/EBP-α. It has been observed that TRIB2 is overexpressed during thymus development, and in B cells, natural killers, and CD4+ T cells and to a lesser degree in CD8+ T cells [ 19 ]. Additionally, TRIB2 is expressed in early hematopoietic progenitors and erythroid precursors, and the deletion of TRIB2 mainly affected erythroid lineage development.…”
Section: Trib2 In Health and Diseasementioning
confidence: 99%
“…In the hematopoietic system, TRIB2 expression is important for lymphoid and erythroid lineages, as it is highly expressed in lymphoid populations, including B, T and NK cells, and moderately expressed in common myeloid progenitor (CMP) and in megakaryocyte–erythroid progenitors (MEP). Conversely, TRIB1 and TRIB3, are more abundant in myeloid lineage and primitive stem cells, respectively [ 19 ]. Although TRIB2 function is fundamental in lymphoid lineage, it is associated with both acute myeloid (AML) and acute lymphoblastic leukemias (ALL).…”
Section: Trib2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The first role for TRIB proteins in haematopoiesis showed that TRIB2 could control the maturation and function of the myeloid and lymphoid lineages in response to cytokines including SCF, G‐CSF, GM‐CSF and M‐CSF . Differential expression of the three TRIB pseudokinases in haematopoietic cells highlights nonredundant and lineage‐specific functions in this system; TRIB1 is expressed most highly in the myeloid lineage, TRIB2 in the lymphoid lineage, and TRIB3 consistently across all haematopoietic cells .…”
Section: Tribbles In Normal Physiologymentioning
confidence: 99%
“…At the transcript level, TRIB1 is highly unstable, reported to have an mRNA half-life shorter than 1 hour (12). TRIB1 expression is also highly variable among different cell types and tissues, suggesting it might be subject to cell type-dependent posttranscriptional regulation (13,14). In fact, the 2kb long, 3'untraslated region (3'UTR) of TRIB1 mRNA represents more than 50% of the entire sequence and is highly conserved among different animal species.…”
Section: Introductionmentioning
confidence: 99%